Nomenclatural notes in Scorpiones (Arachnida) - Acosta, Luis E.; Fet, Victor (Zootaxa, 2005)
Several previous nomenclatural corrections are analyzed and the valid name determined for each case. These include (a) emendations and subsequent spellings: Brachistosternus weijenberghi (Thorell, 1877a) (Bothriuridae), Urophonius iheringi Pocock, 1893 (Bothriuridae), Lisposoma josehermana Lamoral, 1979 (Bothriuridae), Chactas raymondhansi Francke & Boos, 1986 (Chactidae), Tityus fuhrmanni Kraepelin, 1912 (Buthidae), Parabuthus liosoma (Ehrenberg, 1828) (Buthidae), Hadrurus concolorous Stahnke (Iuridae), Vachoniolus minipectenibus (Levy, Amitai & Shulov, 1973); (b) incorrect reversal of precedence: Hadogenes hahni (Peters, 1862) n. comb. (Liochelidae); (c) genus and species names that never were available: Pucha, Puchale, Repucha (Francke, 1985; Fet, 1997), Transbothriurus (Mello-Leitão, 1945; Lowe & Fet, 2000), Scorpio maurus punicus Fet, 2000 (replacement name for Scorpio maurus tunetanus Birula, 1910) (Scorpionidae)